Waktu Aplikasi Kombinasi Trichoberas, Bakteri Endofit, Kulit Jengkol (Pithecellobium jiringa) untuk Menekan Penyakit Bercak Coklat Sempit (Cercospora oryzae) pada Padi Beras Merah (Oryza nivara L.) di Lahan Basah - Putri, Erina Maulida; Budi, Ismed Setya; Mariana, Mariana (www.ulm.ac.id, 2024)
One of the important diseases that attacks red rice plants is narrow brown spot (Cercospora oryzae). Biological control is an alternative that needs to continue to be explored to become an environmentally friendly control solution. The aim of this research was to determine the effect of application time and administration of Trichoberas, endophytic bacteria, jengkol bark in suppressing narrow brown spot disease in red rice in wetlands. Each of these studies used a Completely Randomized Design (CRD) method consisting of 6 treatments which were repeated 4 times so that there were 24 experimental plant units. The results of field research showed that Trichoberas + endophytic bacteria + jengkol peel solution applied three times to red rice plants aged 60, 70 and 80 days could reduce the percentage of infected leaves by 90.63% with a control of 95.95% and an intensity of 48 .01% with a control comparison of 51.69%. The application treatment of Trichoberas + endophytic bacteria + jengkol peel solution on red rice plants aged 80 days (T3) and 60, 70 and 80 days (T5) was able to increase the number of grains, namely 317.25 grains and 325 grains compared to the control 281.75 grains. . The application of Trichoberas + endophytic bacteria + jengkol peel solution to red rice plants aged 60 and 70 days (T4) and aged 60, 70 and 80 days (T5) was able to increase the weight of 1000 grains, namely 18.75 grams and 19.5 grams compared to control 13.25 grams. All treatments were unable to increase plant height growth.